2015
DOI: 10.3892/ijo.2015.3244
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Tyro3 and its implications on hepatocellular carcinoma progression

Abstract: Abstract. While various tyrosine kinases have been associated with the pathogenesis of hepatocellular carcinoma (HCC), the identification of a dominant therapeutic target among them remains a challenge. Here, we investigated the role of Tyro3, a relatively uncharacterized member of the TAM (Tyro3, Axl and Mer) receptor family. The present study aimed to profile and identify potential association between Tyro3 expression in HCC and cancer phenotypes. RNAs obtained from 55 HCC patients were quantified for Tyro3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 21 publications
(24 reference statements)
0
45
0
Order By: Relevance
“…While numerous studies have described signalling pathways downstream of Axl and MerTK and the changes following stimulation with TAM ligands [12,13], relatively few studies have directly assessed signalling pathways downstream of Tyro3, particularly in cancers. Tyro3 was early on found to be autophosphorylated upon overexpression in a ligand-independent manner, and an association with Src kinase was detected [4,26]. In bone, Gas6 was shown to stimulate mouse osteoclast function via Tyro3, involving activation of Erk [22] and Erk signalling mediated Tyro3 regulation of proliferation in breast cancer [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While numerous studies have described signalling pathways downstream of Axl and MerTK and the changes following stimulation with TAM ligands [12,13], relatively few studies have directly assessed signalling pathways downstream of Tyro3, particularly in cancers. Tyro3 was early on found to be autophosphorylated upon overexpression in a ligand-independent manner, and an association with Src kinase was detected [4,26]. In bone, Gas6 was shown to stimulate mouse osteoclast function via Tyro3, involving activation of Erk [22] and Erk signalling mediated Tyro3 regulation of proliferation in breast cancer [27].…”
Section: Discussionmentioning
confidence: 99%
“…Tyro3 knockdown studies in tumour xenograft models have shown a role for Tyro3 in tumour progression, as well as the association of Tyro3 expression with poor prognosis in, amongst others, colorectal, hepatocellular, breast, and bladder cancers [28,36]. Tyro3 has also been linked to Akt signaling and cell survival regulation in e.g., hepatocellular carcinoma [25,26]. Tyro3 shRNA knockdown promoted apoptosis and decreased anchorage-independent growth in e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although foretinib and sorafenib have many common targets, an extended analysis of those unique to each in future trials may shed light on activity differences and inform patient selection. Recent studies reveal certain targets unique to foretinib that deserve further interrogation: TYRO3 was shown to be overexpressed in HCC tumors and linked to HCC cell growth in vitro [30], AXL protein abundance was positively correlated with lymph node metastasis and HCC clinical stage [31], and AXL pathway activation promoted autocrine transforming growth factor-β signaling [32] and invasiveness through activation of SNAI2 [33] in HCC cell lines, as well as HCC xenograft growth in mice [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of Axl and MerTK has been widely reported in many cancer cells [7];[8];[9];[10];[11]. Compared to Axl and MerTK, Tyro3 is the least studied although recently accumulating evidence revealed that the expression of Tyro3 is elevated in several cancer cells such as ovarian cancer, hepatocellular carcinoma, colon cancer and melanoma [12];[13];[14];[15];[16]. For example, Lee reported that overexpression of Tyro3 leads to a resistance in ovarian cancer cells to chemotherapeutic drug taxol [12].…”
Section: Introductionmentioning
confidence: 99%